Pengaruh Struktur Aktiva, Ukuran Perusahaan, dan Profitabilitas Terhadap Struktur Modal Emiten Sektor Telekomunikasi Periode 2000-2006: Sebuah Pengujian Hipotesis Pecking Order - Bram Hadianto (Universitas Kristen Maranatha, 2008)
The aim of this research is to examine pecking order hypothesis with some variables that have impact on capital structure such as asset tangibility, firm’s size, and profitability. The sample that I used was taken from telecommunication sector which collected by purposive sampling method. This research uses panel data analysis as method of analysis. The result concludes that the firm’s size is the only variable that supports pecking order hypothesis.